Hepatopulmonary syndrome: an update - Macêdo, Liana Gonçalves de; Lopes, Edmundo Pessoa de Almeida (São Paulo Medical Journal, 2009)
Hepatopulmonary syndrome (HPS) is a clinical threesome composed of liver disease, intrapulmonary vascular dilatation (IPVD) and arterial gas abnormalities. Its occurrence has been described in up to 32% of cirrhotic candidates for liver transplantation. It also affects non-cirrhotic patients with portal hypertension. Its pathogenesis is not well defined, but an association of factors such as imbalance in the endothelin receptor response, pulmonary microvascular remodeling and genetic predisposition is thought to lead to IPVD. Diagnosis is based on imaging methods that identify these dilatations, such as contrast echocardiography or perfusion scintigraphy with 99mTc, as well as analysis of arterial gases to identify elevated alveolar-arterial differences in O2 or hypoxemia. There is no effective pharmacological treatment and complete resolution only occurs through liver transplantation. The importance of diagnosing HPS lies in prioritizing transplant candidates, since presence of HPS is associated with worse prognosis. The aim of this paper was to review the pathogenetic theories and current diagnostic criteria regarding HPS, and to critically analyze the prioritization of patients with HPS on the liver transplant waiting list. Searches were carried out in the Medline (Medical Literature Analysis and Retrieval System Online) via PubMed, Cochrane Library and Lilacs (Literatura Latino-Americana e do Caribe em Ciências da Saúde) databases for articles published between January 2002 and December 2007 involving adults and written either in English or in Portuguese, using the term hepatopulmonary syndrome. The studies of greatest relevance were included in the review, along with text books and articles cited in references that were obtained through the review.